Practices, representations and discourses of the body. Ambiguity on circus bodies - Infantino, Julieta (2010)
This paper will work the practices of contemporary circus artists in the city of Buenos Aires. We will analyse the way in which corporality can become one of the means of identity expression, given that a social group can compose, through body experiences, its own artistic styles, its own definition of artistic-labour practices, its own legitimate body. We will show how these bodies can at times dispute or reproduce hegemonic conceptions of corporality. We suggest there is a need of thinking these processes in a dynamic way, paying attention to both the mechanisms of power and to its counterpart, the subjects who negotiate, question and/or resist.